Hubungan Komunikasi Bidan dengan Tingkat Kepuasan Ibu Hamil pada Pelayanan Antenatal Care di Puskesmas Gebang Kabupaten Langkat Provinsi Sumatera Utara Tahun 2024 - Kiki Wahyuni; Erin Padilla Siregar; Sri Rezeki; Amelia Erawaty Siregar (Jurnal Ventilator, 2024)
Good communication between midwives and pregnant women greatly influences maternal satisfaction in receiving health services from midwives, so that a sense of mutual trust is built between midwives and pregnant women. This mutual trust will have an impact on changes in attitudes for both service providers and service recipients. the proportion of pregnancy checks in North Sumatra Province was 92.4%, while those who did not have pregnancy checks was 7.6%. The ANC K1 coverage rate in North Sumatra Province was 90.0%, while ANC K4 was 85.9%. This shows that ANC coverage in North Sumatra Province is still low because the national ANC target is 95%. The general aim of this research is to analyze the relationship between midwife communication and the level of satisfaction of pregnant women with ANC services at the Gebang Community Health Center, Langkat Regency in 2024. The research method used is quantitative, information about what you want to know is examined using numerical data through a retrospective survey. Conducting a retrospective survey is one method of collecting historical data. This research uses a cross-sectional strategy. The sample for this in-depth research was all midwives in the Gebang Health Center working area, totaling 40 people. Data analysis uses univariate and bivariate analysis. From the statistical test results, it was obtained that p.value = 0.004 and ? = 0.05, where the value of P.value (0.004) < ? (0.05), so it can be concluded that there is a relationship between midwife communication and pregnant women's satisfaction with antenatal care services in Health Center. Gebang Langkat Regency in 2024. Midwives are expected to further improve their good communication skills with patients by participating in training on effective communication methods so that patients feel satisfied with the services provided.